PEMANFAATAN KOTORAN TERNAK SEBAGAI SUMBER ENERGI ALTERNATIF DAN PENINGKATAN SANITASI LINGKUNGAN - Daru Mulyono (Jurnal Teknologi Lingkungan, 2000)
The effort to discover alternative source of energy in the world is still continued because the dependency from the fossil fuel should be aleviated. Since the energy crisis in 1973, the problem of energy become world hudge intention. In every energy crisis, the price of oil increase sharply and cause lack of stock. Therefore, several countries are trying to diversificate their source of energy. One of the alternative energy is biogas. The biogas can be produced from livestock waste. Through the fermentation processing of livestock waste, it can be produced biogas and the other side product and effect from this processing are: organic fertilizer, animals feeding, and prevent pollution. With the several benefits can be taken from the fermentation of livestock waste, the usage of livestock waste become biogas is necessary to be disseminated in Indonesia, where most of people are living in rural area and depending their livelihood on agriculture.